2017
DOI: 10.1002/acr.23116
|View full text |Cite
|
Sign up to set email alerts
|

Mud‐Bath Therapy in Addition to Usual Care in Bilateral Knee Osteoarthritis: An Economic Evaluation Alongside a Randomized Controlled Trial

Abstract: The results of this cost-effectiveness analysis support the use of MBT as midterm complementary therapy in the management of knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
(44 reference statements)
1
22
0
1
Order By: Relevance
“…Nowadays, several human in vivo studies demonstrated the efficacy of BT [ 1 – 3 , 9 , 48 , 49 ]. Randomized controlled clinical trials investigated OA of the knee [ 50 , 51 ], hip [ 52 ], or shoulder [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, several human in vivo studies demonstrated the efficacy of BT [ 1 – 3 , 9 , 48 , 49 ]. Randomized controlled clinical trials investigated OA of the knee [ 50 , 51 ], hip [ 52 ], or shoulder [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Balneotherapy with mud application is a well-tolerated, costeffective, thermal treatment frequently used for rheumatic diseases, especially knee OA, reinforcing the suitability of this therapy in health systems [21]. The clinical effectiveness of this therapy in OA has been largely demonstrated by numerous investigations [29,30], including studies from our group in the same spa center as the present investigation [14,19].…”
Section: Discussionmentioning
confidence: 61%
“…Several studies have reported the beneficial effects of balneotherapy [15][16][17][18], and particularly mud therapy, on function, perceived pain, analgesic drug consumption, and quality of life in patients with OA, suggesting that they are effective and safe alternatives in the clinical management of this pathology [14,19,20]. Moreover, this strategy is also costeffective, making it a relevant part of the public health systems of many countries within and outside Europe [21,22]. However, despite the evidence of clinical and symptomatic benefits of these therapies, their role in modern medicine is still under discussion [16], mainly because the biological and physiological mechanisms underlying these benefits have not yet been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Ciani et al 69 performed a cost-effectiveness analysis of mudbath therapy alongside a RCT. They found that health related quality of life was significantly improved in the group which received mud-bath therapy compared to the group which received usual care alone.…”
Section: Balneotherapymentioning
confidence: 99%